Dedicated homeless clinics reduce inappropriate emergency department utilization - Chad T. Holmes; Katherine A. Holmes; Andrew MacDonald; Frank R. Lonergan; Joel J. Hunt; Sajid Shaikh; Radhika Cheeti; James P. D'Etienne; Nestor R. Zenarosa; Hao Wang (Journal of the American College of Emergency Physicians Open)
Abstract Background The homeless patient population is known to have a high occurrence of inappropriate emergency department (ED) utilization. The study hospital initiated a dedicated homeless clinic targeting patients experiencing homelessness with a combination of special features. We aim to determine whether this mode of care can reduce inappropriate ED utilization among homeless patients. Methods We conducted a retrospective observational study from July 1, 2017 to Dec 31, 2017. The study enrolled all homeless patients who visited any hospital regular clinic, dedicated homeless clinic, and ED at least once during the study period. ED homeless patients were divided into four groups (A: no clinic visits; B: those who only visited hospital regular clinic; C: those who only visited dedicated homeless clinic; and D: those who visited both hospital regular clinic and dedicated homeless clinic). The New York University algorithm was used to determine appropriate ED utilization. We compared inappropriate ED utilization among patients from these groups. Multivariate logistic regression was used to determine the risks of different clinical visits in association with inappropriate ED utilization. Results A total of 16,323 clinic and 8511 ED visits occurred among 5022 unique homeless patients, in which 2450 unique patients were seen in hospital regular clinic, 784 patients in dedicated homeless clinic, 688 patients in both hospital regular clinic and dedicated homeless clinic, and 1110 patients with no clinic visits. Twenty‐nine percent (230/784) of patients from dedicated homeless clinic utilized the ED, among which 21% (175/844) of their ED visits were considered inappropriate. In contrast, 40% of patients from hospital regular clinic utilized the ED, among which 29% were inappropriate (P < 0.001). The adjusted odds ratio (OR) was 0.61 (95% confidence interval [CI] = 0.50–0.74, P < 0.001) on dedicated homeless clinic predicting inappropriate ED visits in multivariate logistic regression. Conclusion Implementing a dedicated homeless clinic with these features can reduce ED inappropriate utilization among patients experiencing homelessness.